Using the intensity of absorbed gamma radiation to control the content of iron in ore - Azaryan, Albert; Gritsenko, Andrey; Trachuk, Annait; Serebrenikov, Vadim; Shvets, Dmitriy (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports results of mathematical modeling of the intensity of absorbed gamma radiation for determining the iron content in IOR. It was shown that to enhance the accuracy of rapid control of the iron content in IOR, it is advisable to use absorbed gamma radiation. This approach is the improvement of the nuclear-physical method for determining the iron content in IOR. Reflected gamma radiation is used in the existing nuclear-physical methods for determining the iron content in IOR. The gamma-gamma method, the feature of which is the use of "soft" gamma radiation, is used in this method. This leads to the fact that the irradiated surface reflects only a small part of the original flux of gamma radiation. As a result, measuring the intensity of the scattered gamma radiation is characterized by substantial relative errors and, consequently, low-precision of rapid control of iron content in IOR. The use of absorbed gamma radiation as the main part of gamma radiation, makes it possible to significantly reduce the relative error of measurement of the intensity of gamma radiation, that is, to enhance the accuracy of rapid control of the iron content in IOR. The work considered the method of "central geometry" for measuring the intensity of gamma radiation as the most common. This method makes it possible to take into consideration in the mathematical model the dependence of the intensity of absorbed gamma radiation not only on the properties of irradiated surface of rock mass, but also on the geometric parameters in measurement. The main feature of the model is the use of albedo parameter, which allows linking the scattered and absorbed gamma radiation. Representation of the synthesized model in the dimensionless form enabled both simplification of calculations, and generalization of the results of mathematical modeling of the intensity of absorbed gamma radiation. In order to compare the values of intensities of reflected and absorbed gamma-radiation in terms of central geometry, the appropriate numerical calculations were performed. The results of the conducted calculations proved the effectiveness of using absorbed gamma radiation to determine the iron content in IOR. Thus, in the range of 50‒60 percent of the iron content, the sensitivity of absorbed gamma-radiation is considerably higher (by two times) than sensitivity of scattered gamma radiation.